AVARS IN THE TISZA-DANUBE BASIN: SECRETS OF A DISAPPEARED ETHNIC GROUP - Пеняк, Павло (SWorldJournal, 2023)
The article is devoted to the history of the creation of a powerful political union - the Avar Kaganate in the Tisza-Danube basin. The military organization of the Avars, the ethnic composition of the population of the Kaganate, the relations of the Av